2020
DOI: 10.1186/s12960-020-00510-x
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ challenges and factors that motivate them to remain in their workplace in the Democratic Republic of Congo—an interview study

Abstract: Background The Democratic Republic of Congo (DRC) has high maternal mortality and a low number of midwives, which undermines the achievement of goal 3 of the Sustainable Development Goals (SDGs) for 2030, specifically the health of the mother and newborn. Scaling up the midwifery workforce in relation to number, quality of healthcare, and retention in service is therefore critical. The aim of this study was to investigate midwives’ challenges and factors that motivate them to remain in their workplace in the D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Meanwhile it was reported that too many interns crowded around women delivering [70]. In the DRC, midwives reported being placed at departments where their midwifery skills were not utilised, such as surgery/internal medicine wards, the pharmacy, or the administration office [74]. They also noted being shifted across departments according to their supervisor's preferences rather than their professional competence.…”
Section: Part A: Organisational Issues and The Role Of Shortagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile it was reported that too many interns crowded around women delivering [70]. In the DRC, midwives reported being placed at departments where their midwifery skills were not utilised, such as surgery/internal medicine wards, the pharmacy, or the administration office [74]. They also noted being shifted across departments according to their supervisor's preferences rather than their professional competence.…”
Section: Part A: Organisational Issues and The Role Of Shortagesmentioning
confidence: 99%
“…For midwives across settings, not being allowed to practise their profession, not receiving recognition for their work, being unable to influence decisions made by more senior staff or management and experiencing professional disrespect and inferiority within multi-cadre teams, in combination with resource constraints, led to stress, frustration, feeling undervalued, demotivated, demoralised to the point of making it challenging to continue their job [73,74,78]. Being unable to independently take actions that are in the best interest of patients was also argued to contribute to moral distress among nurses in Egypt [79] and Malawi [62].…”
Section: Part A: Organisational Issues and The Role Of Shortagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second main area of action was to create new nursing jobs by 2030, primarily in low- and middle-income countries, to off-set the projected shortages, and to redress the inequitable distribution of nurses across the world. Papers that we have published in the Call include an examination of factors that motivate midwives to remain in their workplace in the Democratic Republic of Congo [ 8 ]; a report on evidence-based health workforce planning and unemployed nurses and midwives in Ghana [ 9 ]; an analysis of the risks of the precarization (casualization) of the Mexican nursing labour market [ 10 ], a study on preferred employment settings of final-year nursing students in Israel [ 11 ], and an international review on burnout in nursing, which takes on even greater prominence with the impact of the pandemic [ 12 ].…”
mentioning
confidence: 99%
“…Only the master trainers were reimbursed, and they judged the compensation level to be too low. This may be explained by the fact, found in another study in the DRC, that healthcare professionals in the DRC, especially nurses and midwives, often lack regular payment or compensation for their employment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%